Design, Synthesis, Molecular Modeling and Anti-HIV Assay of Novel Quinazolinone Incorporated Coumarin Derivatives - Safakish, Mahdieh; Hajimahdi, Zahra; Aghasadeghi, Mohammad R.; Vahabpour, Rouhollah; Zarghi, Afshin (Current HIV Research, 2020)
Background: The emergence of drug-resistant viral strains has created the need for the development of novel anti-HIV agents with a diverse structure that targets key enzymes in the HIV lifecycle. Objective: Considering the pharmacophore of integrase inhibitors, one of the validated targets for anti-HIV therapy, we designed a quinazolinone incorporated coumarin scaffold to affect HIV. Methods: Coumarin is a beta enol ester and also a well-known drug scaffold. Designed structures were prepared using a one-pot three-component reaction from 3-amino-4-hydroxycoumarin, isatoic anhydride and benzaldehyde derivatives. Results: In vitro anti-HIV and cytotoxicity assay indicated that more than half of the compounds had EC50 values lower than 50 μM. Unsubstituted phenyl derivative showed the highest activity and selectivity with an EC50 value of 5 μM and a therapeutic index of 7. Compounds were docked into the integrase active site to investigate the probable mechanism of action. Accordingly, the hydroxyl moiety of coumarin along with the carbonyl of the quinazolinone ring could function as the metal chelating group. Quinazolinone and phenyl groups interact with side chains of IN residues, as well. Conclusion: Here, a novel anti-HIV scaffold is represented for further modification and in-vivo studies.
Keywords: quinazolinone